Staff dissatisfaction in the theatre complex of a private hospital - E.R. Ackerman; M.C. Bezuidenhout (AOSIS, 2007)
The evident job dissatisfaction of nursing personnel in a theatre complex of a private hospital has seemingly led to an extremely high turnover rate of personnel. Several factors appear to be responsible for the discontent among nursing staff such as low staff levels, the continuous quest for cost-effectiveness in terms of staffing numbers, the flexi-time system, insufficiently experienced staff and inadequate care and maintenance of equipment. As a requirement of the C3-Workbook (which sets requirements for staff appraisal) a quantitative, exploratory and descriptive research study was undertaken among all the nursing staff and technicians of a theatre complex in a private hospital. A questionnaire was employed to gather data in this census survey. The aim of the research was to identify the problems in this theatre section in order to take remedial steps in an attempt to re-establish a stable personnel corps which would not only benefit the functioning of the unit but could also contribute to the well being of staff. The findings indicate that dissatisfaction and negative feelings were experienced by the respondents as a result of working conditions, management's lack of support and understanding, unequal distribution of work, unavailability of stock and supplies, remuneration not in line with actual hours worked, the seemingly unfair flexi-time system and insufficient staff numbers. Recommendations were made relevant to management's role, the motivation of staff, shortage of personnel and physical environment.